Brachial neuralgic amyotrophy, a rare disease with serious diagnostic problems - case report - Świerz, Krzysztof; Wacławik, Weronika; Szafraniec, Julia; Szczurek, Katarzyna; Szczepanek, Dawid; Lewoniuk, Natalia; Biesok, Mateusz; Szwancyber, Julianna; Macherski, Maksymilian; Szwinge, Anna (Journal of Education, Health and Sport, 2024)
Neuralgic amyotrophy(NA), is a rare and highly variable neurological disorder of unknown aetiology that causes serious diagnostic problems. We described a case of NA with atrophy of the brachialis muscle in order to enrich clinicians’ knowledge about this disorder and to help them in the proper diagnosis of NA. A 21-year-old man presented with sudden, severe pain in the right biceps muscle. The man had consultations with several doctors and physiotherapists. Three magnetic resonance imaging (MRI) examinations, a nerve conduction study (NCS) and needle electromyography (EMG) were performed. Only after 6 months, based on medical history, physical examination and ultrasound imaging (USI), the physiotherapist suggested NA, which was later on confirmed by a neurologist. This case description of NA showed a variety of symptoms that made it difficult to establish an accurate diagnosis for a longer period of time. The diagnostic procedure, as well as the prolonged time between the onset of symptoms and diagnosis, indicates the need for further education of clinicians to better understand the symptoms of NA.